Aggregation kinetics of different surface-modified polystyrene nanoparticles in monovalent and divalent electrolytes. (December 2019) - Yu, Sujuan; Shen, Mohai; Li, Shasha; Fu, Yueju; Zhang, Dan; Liu, Huayi; Liu, Jingfu
Abstract: The intentional production and degradation of plastic debris may result in the formation of nanoplastics. Currently, the scarce information on the environmental behaviors of nanoplastics hinders accurate assessment of their potential risks. Herein, the aggregation kinetics of different surface-modified polystyrene nanoparticles in monovalent and divalent electrolytes was investigated to shed some light on the fate of nanoplastics in the aquatic environment. Three monodisperse nanoparticles including unmodified nanoparticles (PS-Bare), carboxylated nanoparticles (PS–COOH) and amino modified nanoparticles (PS–NH2 ), as well as one polydisperse nanoparticles that formed by laser ablation of polystyrene films (PS-Laser) were used as models to understand the effects of surface groups and morphology. Results showed that aggregation kinetics of negatively charged PS-Bare and PS-COOH obeyed the DLVO theory in NaCl and CaCl2 solutions. The presence of Suwannee river natural organic matters (SRNOM) suppressed the aggregation of PS-Bare and PS-COOH in monovalent electrolytes by steric hindrance. However, in divalent electrolytes, their stability was enhanced at low concentrations of SRNOM (below 5 mg C L −1 ), while became worse at high concentrations of SRNOM (above 5 mg C L −1 ) due to the interparticle bridging effect caused by Ca 2+ and carboxyl groups of SRNOM. The cation bridging effect was also observed for PS-laser in the presence of high concentrations of divalent electrolytes and SRNOM. The adsorption of SRNOM could neutralize or even reverse surface charges of positively charged PS-NH2 at high concentrations, thus enhanced or inhibited the aggregation of PS-NH2 . No synergistic effect of Ca 2+ and SRNOM was observed on the aggregation of PS-NH2, probably due to the steric repulsion imparted by the surface modification. Our results highlight that surface charge and surface modification significantly influence aggregation behaviors of nanoplastics in aquatic systems. Graphical abstract: Image 1 Highlights: Surface modifications significantly affect aggregation behaviors of NPs. SRNOM stabilized negatively charged NPs by steric repulsion in NaCl solutions. High amounts of SRNOM and Ca 2+ unstabilized negatively charged NPs by cation bridging. SRNOM neutralized or reversed surface charges of NH2 -PS and affect the stability. Abstract : The surface charge and properties of nanoplastics and variability of environmental conditions will control the environmental behaviors of nanoplastics in natural aquatic systems.